Risk Factors For Mortality In Patients Undergoing Thoracic Surgery: A Systematic Review - Faza, Edrine Fatharani; Indah Lestari, Mayang; Novita, Emma (Sriwijaya Journal of Medicine, 2025)
Despite advances in surgical techniques, anesthesia, and perioperative care, complications and mortality in thoracic surgery patients still occur. This study aims to identify risk factors for mortality in patients undergoing thoracic surgery. The database was searched for articles published in 2019–2024 using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols method, and 12 articles met the inclusion criteria. Quality assessment was performed using the Newcastle-Ottawa Scale. A total of 25 mortality risk factors were identified and grouped into three categories, namely preoperative (n = 17), intraoperative (n = 3), and postoperative (n = 5), with preoperative factors as the most dominant category. These results indicate that a thorough evaluation of the patient's condition before surgery, as well as risk mitigation during and after surgical intervention are very important in reducing mortality rates. These findings can be used as a basis for the development of risk stratification and clinical decision making in thoracic surgery patients.